Menuju Zero Waste System Dengan Pendekatan Circular Economy Melalui Pemanfaatan Kain Perca (Studi Kasus Kalangan Penjahit Desa Garawangi Majalengka) - Ryan Abdul Muhit (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
Indonesia from year to year cannot be separated from the problem of waste, especially plastic waste whose impact is different from organic waste. This of course must be immediately prevented and minimized. The Indonesian government has provided several efforts and solutions to prevent this, including the waste-free Indonesia program and the implementation of a circular economy. The method used in this study is qualitative research with field research with qualitative descriptive properties. The results in this study are first, the correlation between circular economy and zero waste in general is the same, namely the essence is the spirit of being based on environmentally friendly (reducing waste). Second, the tailors of Garawangi Village go to zero waste through a circular economy approach, namely by obtaining patchwork or fabric leftover stitches from consumers or customers from the results of fabric cutting, making clothes, or other tailoring which then after obtaining the patchwork is used as a new, more useful item or product. Third, the use of patchwork from consumers by the tailors of Garawangi Village is to only use a reduce and reuse approach from the principle of zero waste and circular economy itself. Keywords: Zero Waste, Circular Economy, Utilization, Patchwork.